2018
DOI: 10.1371/journal.pone.0193775
|View full text |Cite
|
Sign up to set email alerts
|

A comparative morphological revision of the aphid genus Myzaphis van der Goot, 1913 (Insecta: Hemiptera: Aphididae) revealed a new genus and three new species

Abstract: The aphid genus Myzaphis van der Goot, 1913 from the tribe Macrosiphini is revised to include eight species. Apterous and alate viviparous females, known fundatrices and known sexual morphs (oviparous females and males) of Myzaphis bucktoni, M. juchnevitschae, M. rosarum, M. tianshanica and M. turanica are re-described and illustrated. Lectotype and paralectotypes of Myzaphis bucktoni and M. turanica are designated. The status of M. komatsubarae nomen dubium is discussed. Myzaphis avariolosa is regarded as a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…This is similar to the morphs of other Aphididae species, including Myzus persicae and Acyrthosiphon pisum ( Zhang and Zhang 2000 , Kanturski et al 2020 ). However, five type II trichoid sensilla were found at the antennal tip of Aphididae species, including Nippolachnus micromeli and Pseudessigella brachychaeta ( Kanturski et al 2017b , Kanturski et al 2018a ). Furthermore, in alate morphs trichoid sensilla are greater in number than in the corresponding apterous morphs of S. avenae ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the morphs of other Aphididae species, including Myzus persicae and Acyrthosiphon pisum ( Zhang and Zhang 2000 , Kanturski et al 2020 ). However, five type II trichoid sensilla were found at the antennal tip of Aphididae species, including Nippolachnus micromeli and Pseudessigella brachychaeta ( Kanturski et al 2017b , Kanturski et al 2018a ). Furthermore, in alate morphs trichoid sensilla are greater in number than in the corresponding apterous morphs of S. avenae ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Antennae are important in insect sensory systems thanks the role of odorant-binding proteins in host and food searching and mating ( Dahanukar et al 2005 , Scieuzo et al 2021 ) and this is valid for aphids where antenna sensilla play a central role in dispersal, host location, and mating ( Pickett et al 1992 , Zhao and Ban 2011 ). The aphid antennal sensilla are generally divided into trichoid, placoid, coeloconic, and campaniform sensilla ( Zhao and Ban 2011 , Kanturski et al 2018a , Kanturski et al 2018b , Kanturski et al 2020 ). Type I trichoid sensilla are often distributed along antennal segments and serve as mechanoreceptors; type II trichoid sensilla are located at the tip of antennae and serve as mechanoreceptors and chemoreceptors ( Ban et al 2015 , Kanturski et al 2020 ).…”
mentioning
confidence: 99%
“…The specimens were examined using light microscope Leica DM 3000 led and photographed by Leica MC 190 HD camera. The measurements were done according to Ilharco and van Harten (1987) and Kanturski et al (2017) using the Leica LAS system with the LAS Live Measurement pack. Measurements are given in millimetres.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, it is known that aphids feed on hosts in 300 families . Several studies, including Toros et al (2002), Özdemir et al (2005), Görür et al (2012), Kanturski et al (2014Kanturski et al ( , 2018, Şenol et al (2015), Kök et al (2016), Kök & Kasap (2019), Özdemir (2020), have identified more species, hereby increasing the number of aphid species in Turkey to a total of 596 aphid species, 26 of which are subspecies, belonging to 149 genera (Kök & Özdemir, 2021;Patlar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%